Development of complex method of intellectual control in cogeneration systems - Чайковська, Євгенія Євстафіївна (Technology audit and production reserves, 2014)
It is developed a complex method for controlling the operation of the cogeneration system using such dynamic subsystems as: electric accumulator battery, heat electric accumulator; electric accumulator battery, heat pump, which uses a recover heat as a low-grade energy source, which changes as the production of energy and its consumption as a part of a cogeneration unit; biogas plant, heat pump, which uses the fermented wort as a low-potential power source, electric accumulator battery and heat electric accumulator. Predictive information obtaining for decision-making under conditions of not matching production and consumption of electric power and heat can reduce the cost of energy production and emissions of carbon dioxide by 15 %. Biogas saving, for example, by fermentation of 60.2 t/day with increasing marketability of raw biogas unit at 10-15 % is 49400 m3/year.